Relevancia de la contabilidad ambiental, sectorial, auditoría forense y peritaje contable en estudiantes de contabilidad de la Universidad Nacional de la Amazonía Peruana año 2023 - Rojas Lozano, Melannie (2023)
The areas of specialization of accounting are an important aspect in training and professional development, the areas of accounting specialization have not been addressed by studies in the local environment and there are few jobs at other levels, likewise the level is not known. vocational of the students, so with the implementation of the study an attempt was made to cover a gap in knowledge in order to measure if the students are showing due interest or importance in these fields, in that sense the study proposed as a general objective to determine how The relevance of environmental, sectoral accounting, forensic audit and accounting expertise in accounting students of the National University of the Peruvian Amazon in 2023 is presented, for which a descriptive type of research and a descriptive non-experimental design were used, with the participation of 90 accounting major students identifying high levels of importance on the 4 areas of study, that the relevance of the areas in relation to specializing or on job opportunities is high, that the contribution of the areas under study is related to the training received at the university contributing to the knowledge for their academic development, that accounting expertise is the most relevant accounting specialty, followed by forensic auditing, sectoral accounting and finally environmental accounting.